PERIPARTURIENT THIRD DEGREE PERINEAL LACERATION ASSOCIATED WITH RECTO-VAGINA FISTULA AND RECTAL POUCH FORMATION IN A GRADED MURRAH BUFFALO - M. Selvaraju; M. Periyannan; S. Manokaran; S. Prakash; K. Ravikumar; K. Senthilkumar (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A postpartum graded Murrah buffalo that calved 25 days before was presented with a history of swelling of the perianal region immediately after parturition. On examination, ventral anal region was found to be enlarged with a pouch that contained around 1.5 kg of dung. The buffalo was given caudal epidural anaesthesia and the perianal mucous membrane was scarified and sutured. Postoperatively antibiotic, anti-inflammatory and anti-histamine were given for 5 days and animal exhibited normal defecation without straining. The correction of unusual case of peri-partum third degree perineal laceration associated with rectal-vaginal fistula and rectal pouch formation in a graded Murrah buffalo, its management and successful recovery is reported.